2019
DOI: 10.1002/ptr.6502
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plantain syrup on heavy menstrual bleeding: A randomized triple blind clinical trial

Abstract: Given the importance of heavy menstrual bleeding (HMB), we investigated the effect of plantain syrup on HMB. This randomized clinical trial was performed on 68 women with HMB who were referred to the traditional medicine clinics of Mashhad University of Medical Sciences. The intervention group received placebo capsule and plantain syrup, whereas the control group received mefenamic acid capsule and placebo syrup in the first 5 days of menstruation for three menstruation cycles. Patients were asked to complete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…In the study of Khodabakhsh et al, the effect of P. major syrup on heavy menstrual bleeding was investigated and compared with mefenamic acid. The results suggested that this herbal drug may be as effective as mefenamic acid in reducing mensdural bleeding duration (Khodabakhsh et al, 2020). This observed effectiveness is in line with the findings of the current study that showed significant reduction of bleeding duration in herbal drug group.…”
Section: Discussionsupporting
confidence: 90%
“…In the study of Khodabakhsh et al, the effect of P. major syrup on heavy menstrual bleeding was investigated and compared with mefenamic acid. The results suggested that this herbal drug may be as effective as mefenamic acid in reducing mensdural bleeding duration (Khodabakhsh et al, 2020). This observed effectiveness is in line with the findings of the current study that showed significant reduction of bleeding duration in herbal drug group.…”
Section: Discussionsupporting
confidence: 90%